Substrate affinity of the protein tyrosine kinase pp60c-src is increased on thrombin stimulation of human platelets. - Liebenhoff, U (1993)
Human blood platelets contain high levels of non-receptor protein tyrosine kinases of the Src family, particularly pp60c-src, suggesting an important role for these enzymes in platelet physiology. Indeed, in response to various agonists of platelet function, a number of proteins become phosphorylated at tyrosine residues. However, no enzymic activation of an Src-related tyrosine kinase has yet been shown in platelets. In searching for the kinase(s) responsible, we found that all agonists tested that directly or indirectly activate protein kinase C in platelets (phorbol 12-myristate, 13-acetate, thrombin, vasopressin, collagen, calcium ionophore A23187) increased the overall activity of pp60c-src determined by IgG phosphorylation in an immunocomplex assay in the presence of low ATP concentrations. On the other hand, elevation of cyclic AMP directly by forskolin or indirectly by prostaglandin E1, or elevation of cyclic GMP by sodium nitroprusside did not significantly affect the activity of the enzyme. To substantiate the differences in enzyme activity, we determined Km and Vmax, values of pp60c-src from resting and thrombin-stimulated platelets. Thrombin treatment increased substrate affinity of pp60c-src as indicated by a 2- to 3-fold decrease in the Km values for ATP and the exogenous protein substrate casein. Vmax. values were only slightly altered under the assay conditions used. To further rule out modifications of pp60c-src in phosphorylation as a probable cause of the changed substrate affinity, we analysed tryptic phosphopeptides of immunoprecipitated, 32P-labelled pp60c-src of unstimulated and stimulated platelets. The platelet agonists listed above induced an increase in pp60c-src phosphorylation at Ser-12, which is the amino acid phosphorylated by protein kinase C. Surprisingly, we found that elevation of cyclic AMP did not affect 32P labelling of pp60c-src. On the basis of our data, we suggest that phosphorylation at Ser-12 might be one of the signal-triggering events that cause the increase in substrate affinity of pp60c-src.